Melitsah and Haskalah: Towards a Rhetorical Historiography of Modern Hebrew Literature - Banbaji, Amir (MiKAN, 2020)
Melitsah was a venerable term in medieval, Renaissance and Haskalah literary thought. Designated rhetoric, eloquent speech, poetry and rhetorical theory were a focus of  considerable attention during the period of the European Haskalah (1780-1880). Since the mid-19th century, the concept and practice of malitsah became a target of attack, which ultimately led to a sematic change in its meaning. The present article attemps to study the concept of melitsah outside the framework of the massive denunciation it suffered due to the rise of competing literary discources. Stressing the deep affinity between Hebrew melitsah and Renaissance rthetoric, the article provides a brief survey of the term's development, as well as an analysis of its various and often contradictory meanings. The article concludes with a more focused discussion of melitsah theory as was articulated by proponents of Haskalah literature.